In vivo effect of some fungicides on the development of Pyricularia grisea and Helminthosporium oryzae - Douira, A.; Mouria, A.; Ouazzani Touhami, A.; Serghat, S. (Phytopathologia Mediterranea, 2002)
The effect of various fungicide treatments of seeds and leaves of rice on the development of the pathogenicfungi Pyricularia grisea and Helminthosporium oryzae was studied. When applied to seeds, tricyclazole, mancozeband the carboxin+thiram combination were the only fungicides that reduced all the symptoms induced by both pathogenswithout damaging the development of young plants. Tricyclazole and the tricyclazole+mancozeb protected riceplants against P. grisea and H. oryzae respectively throughout the vegetative phase. To ensure protection during theentire vegetative phase, pyrazophos should be applied every two weeks while the carboxin+thiram combination,thiabendazole and mancozeb should be applied every week.